Disease and pest problems of cashew in Malaysia - Lim, T.K; Singh, G. (1979)
In Malaysia, cashew is grown mainly on poor, sandy, marine alluvial soil in the east coast of the Peninsula. Investigations on the failure of fruit setting in bearing trees in plantation holdings in Trengganu and Pahang revealed that the major problems of the cashew crop were not agronomical but rather pathological and entomological in nature. Barreness of trees was found to be due to severe blossom blight and dieback diseases. A spray programme comprising a mixture of fungicide (mancozeb), insecticide (dicrotophos), and a foliar fertiliser surmounted both disease and pest problems and resulted in a significant increase in yield and fruit set.